Numerical Simulation of the Effect of Wind Velocity on the Counter-Rotating Wind Turbines Performance - Irawan, Yosua Heru; Bramantya, Muhammad Agung (University of Muhammadiyah Malang, 2019)
The counter-rotating wind turbines (CRWT) is a wind turbine model developed from a single rotating wind turbine (SRWT) model with a horizontal axis. CRWTs have two rotors rotating in opposite directions on the same axis. The purpose of this research is to investigate the effect of wind velocity on CRWTs performance with different axial distance ratio. The flow around CRWTs is simulated using computational fluid dynamic (CFD) with ANSYS Fluent. The simulation consists of two steps: obtaining the optimum rotation and rotor torque, respectively. These two values are used to calculate the mechanical power of the rotors. In this simulation, the wind velocities are 2 m/s; 3 m/s; and 4.2 m/s. The variations of axial distance ratio are 0.3; 0.5; 0.7; 0.8; and 1. The result of the simulation shows that the optimum ratio of the axial distance will change with the change of wind velocity. Regarding the wind velocity of 2 m/s, the optimal ratio of the axial distance is 0.5. Regarding the wind velocity of 3 m/s and 4.2 m/s, the optimal ratios of the axial distance are 1 and 0.8, respectively.